Who Needs Legal Aid Services? Addressing Demand in Jordan - Prettitore, Paul (World Bank, Washington, DC, 2012)
With the launch of two World Bank-funded programs, Jordan is stepping where few countries in the Middle East and North Africa (MENA) region have gone before the development of comprehensive legal aid services based more closely on demand. For many poor persons, regular avenues of dispute resolution may prove inaccessible due to the costs involved, the complicated nature of procedures, the inability to procure legal information and representation, and a general lack of knowledge about rights and the means to enforce them. Legal aid services information, counseling and representation in court can help poor persons overcome these obstacles. They are not only important as services themselves, but are gateway services they may ultimately lead to access to other services, such as social welfare benefits or basic services.